Promoting the Marketing of Agricultural Products as a Means of Boosting the Nigerian Economy - Offornedu Chima; Owuala Blessing; Dike Kalu; Eziaku Alozie-Oji (ARRUS Journal of Social Sciences and Humanities, 2022)
The agricultural sector in Nigeria is a sector of the Nigerian economy that has the potentials of boosting the country’s economy, create employment and earn the country massive foreign exchange. But due to the country’s over dependence on the oil sector, the agricultural sector has been neglected or not given the attention it deserves. This work tends to highlight how the marketing of agricultural products could boost the Nigerian economy if properly harnessed. It also exposed some problems facing the sector and proffered some possible solutions to these problems.